Iinterorganizational imitation heuristics arising from cognitive frames - Nikolaeva, Ralitza (Journal of Business Research, 2012)
The literature on organizational imitation mostly disregards its cognitive aspect. Yet, imitation is a cognitive heuristic for complex strategic decisions. The current essay draws a unifying framework of different models of imitation through a cognitive lens in the context of innovation adoptions. It describes the interaction of the framing of imitation and the organization’s evaluation of an innovation. This interaction of threat and opportunity categorizations results in the use of various combinations of the two most popular imitation heuristics – “imitate the successful” and “imitate the majority” – as managers decide to copy predecessors in order to improve the status quo or to avoid losing it. Since the framings dictate different imitation timings, the speed of innovation diffusion depends on these interactions. However, as different cognitive frames may trigger the same heuristics, generalizations about the adoption motivation based on its timing can be unrealistic...
Keywords: imitation heuristics; managerial cognition; frames; innovation adoption; Research Subject Categories::SOCIAL SCIENCES::Business and economics